A matter of time - Deshpande, Shashi (Penguin Books, 1996)
"One morning, with no warning, Gopal, respected professor, devoted husband, and caring father, walks out on his family for reasons even he cannot articulate. His wife, Sumi, returns with their three daughters to the shelter of the Big House, where her parents live in oppressive silence: they have not spoken to each other in thirty-five years.